2020
DOI: 10.1001/jama.2020.15543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Inactivated Vaccine Against SARS-CoV-2 on Safety and Immunogenicity Outcomes

Abstract: IMPORTANCE A vaccine against coronavirus disease 2019 (COVID-19) is urgently needed. OBJECTIVE To evaluate the safety and immunogenicity of an investigational inactivated whole-virus COVID-19 vaccine in China. INTERVENTIONS In the phase 1 trial, 96 participants were assigned to 1 of the 3 dose groups (2.5, 5, and 10 μg/dose) and an aluminum hydroxide (alum) adjuvant-only group (n = 24 in each group), and received 3 intramuscular injections at days 0, 28, and 56. In the phase 2 trial, 224 adults were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
794
12
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 766 publications
(903 citation statements)
references
References 31 publications
37
794
12
13
Order By: Relevance
“…One way is to seek immunogens and adjuvants that elicit very strong immune responses such as virus-specific IgG induction, which can be easily monitored. For example, a recent clinical trial showed that an experimental vaccine using inactivated SARS-CoV-2 viruses with alum as the adjuvant only elicited comparable, but not much higher virus-specific IgG production than what we and others observed in hospitalized COVID-19 patients (Xia et al, 2020). Using more potent immunogens and adjuvants to enhance immune responses for stronger SARS-CoV-2 IgG production will be an important early indication for effective development of SARS-CoV-2 vaccines that are highly potent and long-lasting.…”
Section: Dear Editorsupporting
confidence: 43%
“…One way is to seek immunogens and adjuvants that elicit very strong immune responses such as virus-specific IgG induction, which can be easily monitored. For example, a recent clinical trial showed that an experimental vaccine using inactivated SARS-CoV-2 viruses with alum as the adjuvant only elicited comparable, but not much higher virus-specific IgG production than what we and others observed in hospitalized COVID-19 patients (Xia et al, 2020). Using more potent immunogens and adjuvants to enhance immune responses for stronger SARS-CoV-2 IgG production will be an important early indication for effective development of SARS-CoV-2 vaccines that are highly potent and long-lasting.…”
Section: Dear Editorsupporting
confidence: 43%
“…43 Phase 2 trial results of the inactivated SARS-CoV-2 vaccine, constructed by Wuhan Institute of Biological Products and Sinopharm, reported that the geometric mean titers (GMT) of NAbs were 121 and 247 at day 14 after 2 injections in participants receiving vaccine on days 0 and 14 and on days 0 and 21, respectively, displaying only transient and self-limiting adverse reactions. 44 Viral RNA Fig. 1 The immune responses induced by SARS-CoV-2.…”
Section: The Development Of Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…The Ad5-vectored COVID-19 vaccine at 5 × 10 10 viral particles was safe, and induced significant immune responses in the majority of recipients after a single immunization (NCT04341389) [12]. Analysis of 2 randomized phase 1 and phase 2 clinical trials of inactivated vaccine showed that patients had a low rate of adverse reactions and demonstrated immunogenicity (ChiCTR2000031809) [13]. Phase 1/2 single-blind, randomised controlled trial with adenovirus vaccine that expresses the spike protein of SARS-CoV-2 in chimpanzee (ChAdOx1 nCoV-19) showed an acceptable safety profile, and homologous boosting increased antibody responses [14].…”
Section: -Dimension and 3-dimension Studies Demonstratedmentioning
confidence: 99%